ECONOMIC DEVELOPMENT AND CULTURAL DEVELOPMENT ON VIETNAM - Nguyen Minh Tri (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
After nearly 35 years of renovation (from 1986 to present), the growth rate Vietnam’s economy has constantly improved over the years, creating favorable conditions to improve the quality of material life and spiritual life for all people, motivation for sustainable socio-economic development. However, the implementation of linking economic development with cultural development in Vietnam today still exist some restrictions such as: Economic development is not commensurate with the inherent potential of Vietnam, the organization of deployment implements the connection between economic development and asynchoronous cultural development negatively impacted the life of the people. Given that situation, the study of relationships between economic development and cultural development has both theoretical significance and see-off force real. The paper focuses on analyzing the theoretical basis and the status of development economic and cultural development in Vietnam today, thereby offering solutions oriented to further promote the implementation of cohesion between Economic and cultural development in Vietnam in the coming time.